Rational choice and strategic conflicts the subjectivistic approach to game and decision theory - Frahm, Gabriel (De Gruyter, 2019)
"This book is refreshing, innovative and important for several reasons. Perhaps most importantly, it attempts to reconcile game theory with one-person decision theory by viewing a game as a collection of one-person decision problems. As natural as this approach may seem, it is hard to find game theory books that really implement this view. This book is a wonderful exception, in which the transition between decision theory and game theory is both smooth and natural. It shows that decision theory and game theory can go--and, in fact, must go--hand in hand. The careful exposition, the many illustrative examples, the critical assessment of traditional game theory concepts, and the enlightening comparison with the subjectivistic approach advocated in this book, make it a pleasure to read and a must have for anyone interested in the foundations of decision theory and game theory." Andrés Perea (Maastricht University) "Gabriel Frahm's relatively nontechnical book is a bold synthesis of decision theory and game theory from a Bayesian or subjectivist perspective. It distinguishes between decisions, or one-person games, and games with two or more players, but Frahm argues that this distinction is not always necessary--the two kinds of games can be analyzed within a common theoretical framework. He models the dynamics of choice in several different settings (e.g., information may be complete or incomplete as well as perfect or imperfect), including one in which players look ahead and make farsighted calculations on which they base their choices. His book contains many provocative examples that illustrate the advantages of a unified theory of rational decision-making." Steven J. Brams (New York University).